(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Ethical Eco-fashion is sustainable fashion, yet its marketing practices is a topic where we are still in phases and cycles of learning about. The word ethical has been added to the ecological part of the product because though the concept began as niche market and appealed to few consumer, generally found to be of higher social strata or social class in the society. With innovative strategic marketing strategies and tactics, it is being presented before the masses and hence it is a big turn-around towards environmental sustainability. The research study here tries to explore and find out as to how ethics and self of a consumer plays a remarkable role in maintaining the ecological sustainability by purchase of organic or green labelled products. The research also investigates as to how Eco-Fashion is growing, either as fad, or future mantra or utopia in the new millennium. Study also finds out the compelling interest of fashion conglomerates to produce, process and promote – what is eco-friendly and environmentally sustainable, including the maximum possible usage of moral, ethical ways of manufacturing and production of these sustainable, non-harmful products. Interestingly the study aims to find out if the Eco-friendly green products are becoming the mainstream gradually in India and aspects of future consumer buying behaviour in real as well as virtual world.